Exploring the influence of economic development: A field study on OIC countries - Al-Isawi, Alaa Thabit Jasim (Edelweiss Applied Science and Technology, 2024)
The present study explores the influence of economic development on OIC countries. The study analyzes key economic, social, and environmental factors to explore the performance of OIC countries and compare them to other regional and country groupings. Factors such as education, gender equality, health, income, poverty and environmental sustainability are examined. The study tackles the role of Islamic economic principles in development, highlighting the alignment of these principles with modern capitalism while emphasizing justice and ethics in economic activities. The study concludes that the low economic performance of OIC countries is not due to adherence to Islamic principles but to lack of proper implementation. By assessing the “Islamicization” of economic policies and practices, the study aims to provide a holistic view of how Islamic teachings influence economic development and prosperity in OIC countries.